Past and present trends in literary translation studies - Milton, John (1990)
This thesis looks at a number of important theories of literary translation and shows that John Dryden\'s triadic division of translations into metaphrase, paraphrase and imitation has been central to the theory of literary translation studies right to the present day. Indeed, the ideas of the French belles infidéles, the German Romantics, Ezra Pound and much contemporary writing on translation fit into Dryden\'s paradigm. Only in recent years do we find ideas which challenge this dominance. Now we can find translation studied as a principal force in the development of literatures. Its mystical element has been examined. Translation can be political. lndeed, translation is increasingly seen as a central buman activity.